2021
DOI: 10.1177/17562848211033730
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention in Barrett’s esophagus and esophageal adenocarcinoma

Abstract: There has been a dramatic increase in the incidence of Barrett’s esophagus and esophageal adenocarcinoma over the past several decades with a continued rise expected in the future. Several strategies have been developed for screening and surveillance of patients with Barrett’s esophagus and endoscopic treatment of Barrett’s associated dysplasia and early esophageal cancer; however, they have not made a substantial impact on the incidence of cancer. Herein, chemoprevention becomes an attractive idea for reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The protective effect was increased with the combined use of both (HR = 0.22; 95% CI 0.06–0.85) [ 68 ]. Other case-control studies have also supported the association between statin use and a reduction in EAC risk [ 69 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 85%
“…The protective effect was increased with the combined use of both (HR = 0.22; 95% CI 0.06–0.85) [ 68 ]. Other case-control studies have also supported the association between statin use and a reduction in EAC risk [ 69 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 85%
“…Taking into account the role of acid secretion in esophageal epithelial damage, proton pump inhibitors appear to be actually the only treatment that can interfere with the worsening of histological damage. Indeed, numerous studies have shown that acid-suppressing proton pump inhibitor therapy stabilizes the activity of cellular proliferative cells in the BE and consequently can prevent dysplasia and have a positive impact on reducing the risk of cancer in the esophagus [ 61 , 62 , 63 , 64 , 65 , 66 ] especially if the therapy is continuous and long-term [ 67 ]. The mechanism by which proton pump inhibitors exert a protective effect is nonetheless unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In BE, metaplastic cells have a higher proliferative rate and are in line with what has been demonstrated both in vitro and in vivo, in esophageal adenocarcinoma cell lines under acid exposure through the production of agents by mitogens that transmit signals regulating cell growth and proliferation, and contextually decrease apoptosis [ 64 ]. Hillmann et al [ 67 ] and other Authors [ 63 , 64 , 65 ], demonstrated that these drugs stabilize the proliferation of epithelial cells already in the short term suggesting that the prolongation of the duration will limit the hyperplasia of the basal cell layer [ 68 , 69 ]. Our results are in agreement with this hypothesis; we monitored the patients after one year of follow-up by observing a decrease in Ki67 expression, a sign of a decrease in cell proliferation, and contextually a decrease in FAS-mediated supplementary metabolic activities, a sign of loss of cellular metabolic demand.…”
Section: Discussionmentioning
confidence: 99%
“…Silicosis caused by asbestos fibers or silica dust is related to lung cancer 21 . Barrett's esophagitis is related to esophageal cancer 22,23 …”
Section: Inflammation and Tumorsmentioning
confidence: 99%